2006
DOI: 10.1007/s10740-006-0009-z
|View full text |Cite
|
Sign up to set email alerts
|

The second and third virial coefficients of simple fluids

Abstract: The asymptotic behavior of the second B and third C virial coefficients in the low temperature region is analyzed for fluids with a spherical pair-additive potential of interparticle interaction. The temperature dependences B(T) and C(T) are approximated by expressions which convey correctly the behavior of the virial coefficients in the low-and high-temperature limits. The free parameters of approximation formulas for pure nitrogen, argon, and oxygen are determined. The derived virial equations of state are u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0
3

Year Published

2010
2010
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 19 publications
0
4
0
3
Order By: Relevance
“…Measurements of adsorption isotherms were also described in detail elsewhere. , Capillary condensation and evaporation pressures of nitrogen in the ordered mesoporous silicas at various temperatures were reproduced from our previous studies. , The condensation and evaporation pressures were transformed to fugacities using the second and third virial coefficients, in order to compare with theoretical results.…”
Section: Methodsmentioning
confidence: 99%
“…Measurements of adsorption isotherms were also described in detail elsewhere. , Capillary condensation and evaporation pressures of nitrogen in the ordered mesoporous silicas at various temperatures were reproduced from our previous studies. , The condensation and evaporation pressures were transformed to fugacities using the second and third virial coefficients, in order to compare with theoretical results.…”
Section: Methodsmentioning
confidence: 99%
“…Para el ajuste de B 3 experimental y B 3 calculado con el potencial de Lennard-Jones, utilice mínimos cuadrados, similar al ajuste de B 2 , pero tomando más términos, este coeficiente es más difícil de ajustar, Boltachev [2] represento B 3 reducido como combinación lineal de potencias inversas con exponenciales, tomando esto como precedente, el B 3 que proponemos es de la forma…”
Section: Resultsunclassified
“…El término 6V b 3 esta dado por la ecuación anterior y ahora escribimos en forma conveniente 12V b 2 2 para restarlo de 6V b 3 . Sabemos que…”
unclassified
See 1 more Smart Citation
“…Obviously, for all of the potentials, this quantity curves at the lower and higher temperatures. Botachev and Baidakov suggested that most of the second virial coefficient data are in the temperature range of (0.5 − 3) T c which corresponds approximately to a reduced temperature range of 0.5 < T * < 4.0 for a Lennard−Jones fluid. We have considered the reduced temperature range of 0.3 < T * < 10.0 and plotted the ( T * − T Boyle * )/ B * quantity versus T * 1.1 for different second virial coefficients from different pair potentials.…”
Section: Resultsmentioning
confidence: 99%